1992
DOI: 10.1007/bf00994240
|View full text |Cite
|
Sign up to set email alerts
|

Female sex pheromone of oriental tobacco budworm,Helicoverpa assulta (Guenee) (Lepidoptera: Noctuidae): Identification and field testing

Abstract: Analysis of ovipositor washings from virgin femaleHelicoverpa assulta (Guenée) (Lepidoptere: Noctuidae) from Korea by gas chromatography (GC) linked to electroantennography and GC linked to mass spectrometry resulted in the identification of nine compounds, hexadecanal, (Z)-9-hexadecenal, (Z)-11-hexadecenal, hexadecyl acetate, (Z)-9-hexadecenyl acetate, (Z)-11-hexadecenyl acetate, hexadecan-l-ol, (Z)-9-hexadecen-l-ol, and (Z)-11-hexadecen-1-ol. However, ovipositor washings from females from Thailand contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 28 publications
3
55
0
Order By: Relevance
“…Whereas most of the species rely on cis-11-hexadecenal (Z11-16:AL) as the major pheromone component, H. assulta utilizes this substance as the second component, and cis-9-hexadecenal (Z9-16:AL) as the major one (Sugie et al, 1991;Cork et al, 1992;Park et al, 1994). The optimal ratio between the major and the second principal pheromone component is 20:1 in the Korean population of H. assulta (Cork et al, 1992). …”
mentioning
confidence: 99%
“…Whereas most of the species rely on cis-11-hexadecenal (Z11-16:AL) as the major pheromone component, H. assulta utilizes this substance as the second component, and cis-9-hexadecenal (Z9-16:AL) as the major one (Sugie et al, 1991;Cork et al, 1992;Park et al, 1994). The optimal ratio between the major and the second principal pheromone component is 20:1 in the Korean population of H. assulta (Cork et al, 1992). …”
mentioning
confidence: 99%
“…Helicoverpa assulta and Helicoverpa gelotopoeon Z9-16:Ald has assumed a primary role in the pheromone blend [Cork et al, 1992;Cork and Lobos, 2003] and Z11-16:Ald has either been relegated to a secondary role ( H. assulta ) or eliminated from the blend altogether ( H. gelotopoeon ). Interestingly, Z9-14:Ald is inhibitory to H. assulta males and appears to maintain reproductive isolation between this species and several other heliothine species with which its range overlaps to a greater or lesser extent [Boo et al, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…1). & Yang, 2000 communication in this species (Cork et al, 1992;Park et al, 1994a). Leaf extracts of Capsicum annum, a major host-plant, evoked significant electroantennogram (EAG) responses in female H. assulta, which could be related to the observation that females showed more actively calling behavior and produced a larger amount of sex pheromone in the presence of the host-plant (Boo and Ahn, 2001).…”
Section: The Oriental Tobacco Budwormmentioning
confidence: 92%
“…Boo, 1988), and histological observation showed the location of a sex pheromone gland at the 8-9th abdominal segments (Moon et al, 1986), which were in close agreement with those reported for other Heliothis/Helicoverpa and other moth species. Shortly after, chemical identification was accomplished in collaboration with British scientists (Cork et al, 1992), and the results were published a year after a Japanese group reported sex pheromone composition of H. assulta in Japan (Sugie et al, 1991). Interestingly, the most abundant sex pheromone component of H. assulta was (Z)-9-hexadecenal (Z9-16:Ald), which was exactly the opposite from other known Heliothis and Helicoverpa species whose major pheromone component was (Z)-11-hexadecenal (Z11-16:Ald).…”
Section: The Oriental Tobacco Budwormmentioning
confidence: 99%
See 1 more Smart Citation